Experimental analysis of different GSM of glass fibre using dynamic mechanical analysis. (2020) - Khurana, Ishant; Pratap, Chandra; Singh, Shubhender; Bansal, Ankit; Butola, Ravi
Abstract: The aim of the study is to investigate the dynamic mechanical properties of different samples viz. 200, 250, 300, 600 GSM (Gram per Square Metre) of glass fibres through Dynamic Mechanical Analysis (DMA). DMA is a technique that is widely used to characterize a material's properties as the variation of dynamic properties (Storage modulus, Loss modulus and tan δ) with respect to time and temperature. The increase in GSM of the samples leads to increase in glass transition temperature (Tg). The analysis shows that the orientation of the fibre played a crucial role in determination of storage modulus. It was found that the storage modulus for 45° orientation was more than that for 0° orientation and further concluded that the glass transition temperature influenced the static displacement.